Efeitos funcionais e sistêmicos do pós-operatório recente de cirurgia bariátrica: treinamento físico com eletroestimulação de corpo inteiro como estratégia de reabilitação precoce - André, Larissa Delgado (2020)
Obesity is a chronic inflammation and multifactorial disease associated with comorbidities and has reached alarming epidemic proportions worldwide. Bariatric surgery (BS) has been considered the most effective treatment, being Roux-en-Y gastric bypass the most prevalent approach. The surgical procedure associated with physical inactivity and restrictive hypocaloric dietary in the postoperative (PO) period decrease weight loss, also followed by muscle mass loss and, consequently lower functional and aerobic capacity, affecting muscle quality. In this context, being important to understand the mediate consequences of surgery as well as to promote early rehabilitation strategies, we proposed the accomplishment of two studies. The first one, a prospective and observational study, entitled “Impact of bariatric surgery on submaximal exercise testing in morbid obese patients” aimed to evaluate the mediate effects of bariatric surgery by means of body composition with bioimpedance and functional capacity applying the 6-minute walking test (6MWT) before and early after hospital discharge. Thirty-nine morbid obese who underwent RYGB were included. In our findings, impairments on aerobic and functional capacity with significant reduction of distance walked in the 6MWT as well as cardiometabolic and pulmonary variables and significant decline in all body composition measures, emphasizing the crucial loss of muscle mass in one week post-BS. Thereafter, due to negative consequences of BS, the study II, a randomized triple blind controlled trial, entitled “Whole-body electrical stimulation as a strategy to improve functional capacity and preserver lean mass after bariatric surgery: a randomized triple-blind controlled trial was developed. Thirty-five obese, aged between 18 and 45 years old, were submitted to RYGB. The preoperative assessments consisted of maximal and submaximal exercise testing, body composition analysis, blood collection and quadriceps strength and endurance test. The PO evaluation, performed between two days to one week after discharge, was carried out with measurements of body composition and 6MWT and after completion of intervention protocol, all preoperative evaluations were repeated. In the intervention protocol, randomized subjects performed electromyostimulation group (WB-EMSG, n=17) or control group (ShamG, n=18). The protocol consisted of 10-14 dynamic exercises, with no load, 5 days per week, for a total of 30 sessions. Both groups wore WB-EMS vests, which only WB-EMSG underwent an electrical stimulation protocol (Endurance: 85Hz, 350ms, 6s of strain, 4f of rest; Strength: 30Hz, 350ms, 4s of strain, 10 ABSTRACT seconds of rest, with bipolar electrical pulse). After intervention, subjects were reevaluated and ShamG performed same protocol with switched off current. The main findings of the present study were: 1) both intervention protocols demonstrated favorable outcomes on functional capacity performance but only WB-EMSG reached important amelioration of the same measures when compared to preoperative baseline, followed by decreased blood pressure, leg fatigue and dyspnea during recovery; 2) both groups demonstrated similar improvements in body composition parameters; 3) WB-EMS avoided greater loss of muscle strength and endurance following the intervention; a significant decline in muscle performance and important increase in muscle fatigue was only apparent in the ShamG; and 4) WB-EMSG was not superior to exercise training alone in improving biochemical parameters but did lead to a significant increase in adiponectin. In conclusion, the mediate PO is associated with reduction of body composition, especially lean mass and impairments on functional capacity, highlighting the importance of early evaluation and intervention rehabilitation. Additionally, a 6-week WB-EMS program associated with dynamic exercises in post-BS patients improved functional capacity, preserved muscle strength and endurance, with maintenance of muscle fatigue. However, WB-EMS was not able to enhance the effects of body weight reductions acutely following BS. Our results are important to show the feasibility of applying early rehabilitation protocols in morbidly obese patients after BS, and that WB-EMS may potentiate the positive effects of an exercise training program, being well tolerated and promoting adherence among post-BS patients.